Practical issues in measuring the anticoagulant effect of direct oral anticoagulants - Dopsaj, Violeta (Archives of Pharmacy, 2020)
The classical oral anticoagulants are increasingly being replaced in clinical practice by new antithrombotic drugs, which act by enabling direct inhibition of coagulation factor IIa (FIIa) or factor Xa (FXa). These drugs have multiple acronyms, including NOACs (new, non–vitamin K antagonist) or DOACs (direct oral anticoagulants), and currently include dabigatran (FIIa inhibitor), and rivaroxaban, apixaban, and edoxaban (FXa inhibitors). These drugs are approved for stroke prevention in patients with non-valvular atrial fibrillation and the prevention and treatment of venous thromboembolism. The "mantra" that DOACs do not require laboratory monitoring is not entirely correct because laboratory testing for drug effects is needed in many situations, because they influence hemostasis tests and in situations in which urgent measurement of DOACs is required. This should be very important to consider in the clinical situation for numbers of indications and increasing numbers of patients on DOACs therapy. The main aim of this article is to provide practical issues to general laboratory testing for DOACs, as well as to help avoid diagnostic errors associated with hemostasis testing. The assays for DOAC quantification must be available in medical centers on a whole day basis, to facilitate optimal drug management in conditions when things go wrong or in urgent cases of immediate reversal of anticoagulation or appropriate administration of a specific antidote.